2008
DOI: 10.1177/0192623308327121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of p38 MAP Kinase Inhibitors on the Differentiation and Maturation of Erythroid Progenitors

Abstract: In rodents, p38 MAP kinase inhibitors (p38is) induce bone marrow hypocellularity and reduce reticulocyte and erythrocyte counts. To identify target cell populations affected, a differentiating primary liquid erythroid culture system using sca-1 + cells from mouse bone marrow was developed and challenged with p38is SB-203580, SB-226882, and SB-267030. Drug-related alterations in genes involved at different stages of erythropoiesis, cell-surface antigen expression (CSAE), burst-forming unit erythroid (BFU-E) col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…These findings suggest that G-CSF treatment might be important in promoting the recovery of hematopoiesis immediately after TBI, which is consistent with the previous reports [27], [28], [29], [30]. It has been shown that p38 inhibition can modulate hematopoiesis as well [31]. In this study, we found that inhibition of p38 with SB alone promoted the recovery of WBC, RBC and PLT at 30d post irradiation, but its effects were not significant at 10d post irradiation.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that G-CSF treatment might be important in promoting the recovery of hematopoiesis immediately after TBI, which is consistent with the previous reports [27], [28], [29], [30]. It has been shown that p38 inhibition can modulate hematopoiesis as well [31]. In this study, we found that inhibition of p38 with SB alone promoted the recovery of WBC, RBC and PLT at 30d post irradiation, but its effects were not significant at 10d post irradiation.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we analysed the expression of other markers which can be associated with hematopoietic stem/progenitor cells. Unexpectedly, the expressions of Sca1 and c-Kit were increased in contrast to the overall decrease in haematopoiesis in p38 α −/− cells but this could be explained as a delay in the differentiation process [14, 57]. In contrast, lower expressions of CD34 transcripts in mutant cells mark a decrease in hematopoietic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that EPO activity is mediated by p38 α kinase and that p38 α kinase is required for EPO mRNA stability and hemoglobin synthesis. Moreover, the inhibition of p38 α leads to the blocking of the EPO-dependent accumulation of mouse globin chains in erythroid precursors [14, 57]. Also, erythrocyte maturation is impaired not only by defects in EPO/EpoR downstream signaling but also by a low level of EpoR transcript, the expression of which is induced by GATA1 [61].…”
Section: Discussionmentioning
confidence: 99%
“…Using the inhibitors SB203580 and p38 MAPK inhibitor III they showed that inhibition of p38 kinase leads to reduced PS exposure upon hyperosmotic shock or ionomycin stimulation [ 63 ]. Other studies employing pan p38 inhibitors demonstrate that p38 MAPK inhibition induces a transient delay in murine erythropoiesis [ 64 ]. In vivo experiments with p38 MAPK knockout mice show that mice die in utero or survive owing to severe anaemia due to defective erythropoiesis resulting from reduced erythropoietin (Epo) levels [ 65 ].…”
Section: Discussionmentioning
confidence: 99%